The ALMA survey to Resolve exoKuiper belt Substructures (ARKS) V. Comparison between scattered light and thermal emission - Perez-Marquez, S (EDP Sciences, 2026)
Context. Debris discs are analogues to our own Kuiper belt around main-sequence stars and are therefore referred to as exoKuiper belts. They have been resolved at high angular resolution at wavelengths spanning the optical/near-infrared to the submillimetre-millimetre regime. Short wavelengths can probe the light scattered by such discs, which is dominated by micron-sized dust particles, while millimetre wavelengths can probe the thermal emission of millimetre-sized particles. Determining differences in the dust distribution between millimetre- and micron-sized dust is fundamental to revealing the dynamical processes affecting the dust in debris discs. Aims. We aim to compare the scattered light from the discs of the ‘ALMA survey to Resolve exoKuiper belt Substructures’ (ARKS) with the thermal emission probed by ALMA. We focus on the radial distribution of the dust, and we also put constraints on the presence of giant planets in those systems. Methods. We used high-contrast scattered light observations obtained with VLT/SPHERE, GPI, and the HST to uniformly study the dust distribution in those systems and compare it to the dust distribution extracted from the ALMA observations carried out in the course of the ARKS project. We also set constraints on the presence of planets by using these high-contrast images combined with exoplanet evolutionary models. Results. Fifteen of the 24 discs comprising the ARKS sample are detected in scattered light, with TYC 9340-437-1 being imaged for the first time at near-infrared wavelengths. For six of those 15 discs, the dust surface density seen in scattered light peaks farther out compared to that observed with ALMA. These six discs except one are known to also host cold CO gas. Conversely, the systems without significant offsets are not known to host gas, except one. Moreover, with our scattered light near-infrared images, we achieve typical sensitivities to planets from 1 to 10 MJup beyond 10 to 20 au, depending on the system age and distance. Conclusions. This observational study suggests that the presence of gas in debris discs may affect the small and large grains differently, pushing the small dust to greater distances where the gas is less abundant. © The Authors 2026.